PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, PELATIHAN KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA HONEYMOON GUESTHOUSE UBUD - Ni Putu Arik Esmayani; Pande Ketut Ribek; Tiksnayana Vipraprastha (VALUES, 2024)
The success and failure of a company is often determined by the important role of its human resources. There aremany factors that influence employee performance, including transformational leadership issues, job training and compensation. Likewise at Honeymoon Guesthouse Ubud, transformational leadership, job training and compensationare factors that can influence employee performance. There is attention and findings regarding the issues of transformational leadership, job training and compensation in an effort to improve and increase employee performance in accordance with the aim of this research to determine the influence of transformational leadership, jobtraining and compensation on employee performance at Honeymoon Guesthouse Ubud. The population in this study was 45 people. The number of samples in this study was 45 people. The sampling technique used is the saturated sample method. Data analysis in this study used Multiple Linear Regression Analysis using the IBM SPSS Statistics 25 application. The research results show that 1) Transformational leadership has a positive and significant effect on employeeperformance at Honeymoon Guesthouse Ubud. 2) Job training has a positive and significant effect on employeeperformance at Honeymoon Guesthouse Ubud. 3) Compensation has a positive and significant effect on employee performance at Honeymoon Guesthouse Ubud.